Examination of Ecological Systems Contexts Within a Latino-Based Community Sport Youth Development Initiative - Robledo, Mayra V.; Edwards, Michael B.; Bocarro, Jason N.; Behnke, Andrew O.; Casper, Jonathan M. (Frontiers in Sports and Active Living, 2022)
Youth Development Programs (YDPs) can serve as effective mechanisms to alleviate social and psychological adversities while enhancing and developing resilience among youth. Recently, more YDPs have incorporated sport within Sport for Development (SFD) models to achieve these goals. Due to the growing Latino population in the US and the wide achievement gap between Latinos and other demographic populations, there is a need to explore programs that may support individual development as well as long-term change with regard to social inequality. There is also a need to better understand the ecological contexts within SFD programs and how these contexts may support underserved youth. Specifically, using an ecological systems perspective, this study seeks to explore the implementation of a sport program by a YDP in order to examine the ecological processes that may support or inhibit the efficacy of sport programs working with underserved youth. Juntos is a YDP that primarily serves Latinx youth and families by assisting youth with graduating high school and pursuing higher education opportunities. Juntos incorporates two annual soccer tournaments (i.e., Kicking it with Juntos and Copa Unidos). A qualitative case study approach was implemented in two counties in North Carolina. Interviews were conducted with tournament participants, county coordinators and planning committee members. Findings found three key themes related to three ecological levels 1. At the Microsystem level, sport was implemented to engage youth and connect to non-sport program outcomes, but divergent perceptions of goals among stakeholders potentially inhibited intentional implementation. At the Mesosystem level, sport provided a mechanism to engage in collaborative relationships and encouraged parental participation. At the Macrosystem level, sport celebrated Latino culture and attempted to address social barriers facing Latinx youth, but some aspects of culture may have created barriers to access for girls. Findings suggested that while the programs emphasized mesosystem engagement, more integration across exosystem and macrosystem levels may be needed for sustainable outcomes.